Synthesis of chlorophyll thin film from hibiscus leaves by dip coating sol-gel process - Muhammad Syafie Bin Ahmad (School of Material Engineering, University Malaysia Perlis, 2016)
In this project, the chlorophyll extracted from the hibiscus leaves was deposited on the glass substrate by using dip coating technique to produce chlorophyll thin film. The chlorophyll thin film was dried at three different temperatures of 300C, 50C and 70C. The effect of different drying temperatures on the surface morphology and composition of chlorophyll thin film were investigated. The result shows that grain structure will gradually shrink when the temperature increase. It will form an island shape stucture known as Volmer-veber growth. Besides that, the presence of magnesium indicate that thin film contain chlorophyll pigment. Higher absorption of chlorophyll leads to higher electricity conversion.